2012
DOI: 10.1080/07399332.2012.655384
|View full text |Cite
|
Sign up to set email alerts
|

Space, Agency, and Withdrawal: Birth Control Choices of Women in Turkey

Abstract: Withdrawal (WD) is not a reliable method for preventing unwanted pregnancies, yet it is still a very popular form of birth control in many societies, including Turkey. We look at the relationship between women's agency and physical space in relation to birth control choices of women in Turkey. Agency in our context refers to a woman's ability to resist domination and subordination to the patriarchal beliefs valuing her reproductivity over her pleasure. Our analysis of the Turkish Demographic Health Survey (TDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Conversely, based on the results of multivariate analysis, the likelihood of using withdrawal was lower among women with primary education compared to more educated women. Other studies (21,22) found that there was less likelihood of using withdrawal among illiterate and primary women compared to those with college degrees.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, based on the results of multivariate analysis, the likelihood of using withdrawal was lower among women with primary education compared to more educated women. Other studies (21,22) found that there was less likelihood of using withdrawal among illiterate and primary women compared to those with college degrees.…”
Section: Discussionmentioning
confidence: 92%